Photographic science advances in nano-particles, J-aggregates, dye sensitization, and organic devices - Tani, Tadaaki (Oxford : Oxford University Press, 2011)
This book provides a guide to modern developments in photographic science and their possible applications to new and exciting areas, including nano-technology, solar cells, and organic semiconductors.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Photographic chemistry; Photography -- Scientific applications